1993
DOI: 10.1042/bj2920485
|View full text |Cite
|
Sign up to set email alerts
|

Human inter-α-inhibitor family in inflammation: simultaneous synthesis of positive and negative acute-phase proteins

Abstract: The inter-alpha-inhibitor (I alpha I) family encompasses four plasma proteins, namely free bikunin as well as I alpha I, pre-alpha-inhibitor (P alpha I) and inter-alpha-like inhibitor (I alpha LI). Each of the last three proteins is a distinct assembly of one bikunin chain with one or more unique heavy (H) chains designated H1, H2 and H3. The three H chains and the bikunin chain are encoded by four distinct mRNAs. These molecules and chains, as well as the corresponding mRNAs, were quantified in sera and liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
66
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 37 publications
10
66
0
Order By: Relevance
“…The hepatic level of fetuin-A mRNA is down-regulated during an APR in rat [23,26] and our preliminary data indicated that the hepatic level of fetuin-B mRNA also varies following an inflammatory challenge in rat [27]. Therefore, we compared in more detail the changes of both mRNA levels of both genes in liver during an APR in rat.…”
Section: Inflammation-associated Changes In Hepatic Level Of Fetuin-bmentioning
confidence: 95%
See 3 more Smart Citations
“…The hepatic level of fetuin-A mRNA is down-regulated during an APR in rat [23,26] and our preliminary data indicated that the hepatic level of fetuin-B mRNA also varies following an inflammatory challenge in rat [27]. Therefore, we compared in more detail the changes of both mRNA levels of both genes in liver during an APR in rat.…”
Section: Inflammation-associated Changes In Hepatic Level Of Fetuin-bmentioning
confidence: 95%
“…Older animals were killed by cervical dislocation (mouse) or by anaesthesia with ethyl ether (rat). An acute systemic inflammation was induced in adult male rats by a single injection of bacterial lipopolysaccharides (LPS) or Freund's complete adjuvant (FCA) given intraperitoneally or turpentine oil (TO) given subcutaneously, as detailed previously [26,27].…”
Section: Animals and Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a glycoprotein of M r 125,000 composed of one heavy chain of M r 90,000, called HC3, and one light chain of M r 16,000, bikunin carrying the glycosaminoglycan (14). The level of pre-␣-trypsin inhibitor, an acute-phase protein, rises in response to trauma and inflammation (16). In the pathological synovial fluid from human arthritis patients, HC3 is covalently bound to hyaluronan (17).…”
mentioning
confidence: 99%